Identifikasi Kesegaran Ikan Berdasarkan Citra Insang dengan Metode Convolution Neural Network - Miftahus Sholihin (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
This study aims to create a fish freshness identification system based on the image of fish gills. With this system, it is hoped that the community will find it easier to determine fresh fish. The method used in this study is CNN. The data used in this study amounted to 150 fish gill image data which were categorized into three classes, namely fresh, not fresh, and rotten fish classes. This research provides 100% accuracy for the training process and 97.7% for the testing process.